Covalent vs. Dative Bonding in Carbon Monoxide and Other 10-Valence-Electron Diatomics - Khadija Rizwan; John Morrison Galbraith (Molecules)
Valence bond theory (VB) was used to determine the extent and driving forces for covalent vs. dative bonding in 10-valence-electron diatomic molecules N2, CO, NO+, CN−, P2, SiS, PS+, and SiP−. VBSCF calculations were performed at the CCSD(T)/cc-pVDZ optimized geometries. The full triply bonded system included 20 VB structures. A separation of the σ and π space allowed for a subdivision of the full 20 structure set into sets of 8 and 3 for the π and σ systems, respectively. The smaller structure sets allowed for a more focused look at each type of bond. In situ bond energies for σ bonds, individual π bonds, the π system, and triple bonds follow expected trends. Our data shows that N2 and P2 have three covalent bonds whereas CO and SiS contain two covalent and one dative bond, and charged species NO+, CN−, PS+, and SiP− are a mixture of N2 and CO type electronic arrangements, resulting in a nearly equal charge distribution. Dative bonds prefer to be in the π position due to enhanced σ covalency and π resonance. Both σ and π resonance energies depend on a balance of ionic strength, orbital compactness, σ constraints, and bond directionality. Resonance energy is a major contributor to bond strength, making up more than 50% of the π bonds in SiS and PS+ (charge-shift bonds), and is greater than charge transfer in dative bonds.